How to establish uniform higher education quality management system for Macedonia - Violeta Milenkovska; Blagica Novkovska (UTMS Journal of Economics, 2018)
Total quality management of higher educational institutions is of paramount importance for modern society and presents a growing interest for researchers. In this paper the issue of effective establishment of total quality management system in higher education in Macedonia is discussed in details. Current situation of the system and the legislative environment are discussed. It has been found that after significant changes in the system, stable developed legal environment has been established. Variations of the number of graduate students in the period 2000-2016 have been discussed in details and the origin of variations identified. Saturation of this indicator in the last decade was observed and its origin has been explained. Based on experiences from other countries with developed higher educational system, proposals for establishing an efficient total quality management system for the case of Macedonia are made. A detailed model for establishment of a common total quality management system is proposed.
Keywords: I21; I29; K39; 330; Bologna system; electronic administrative services; low on higher education; business process modelling